2014
DOI: 10.1111/ajsp.12099
|View full text |Cite
|
Sign up to set email alerts
|

Culture and decision‐making: Investigating cultural variations in the East Asian and North American online decision‐making processes

Abstract: Research in cross-cultural psychology suggests that East Asians hold holistic thinking styles whereas North Americans hold analytic thinking styles. The present study examines the influence of cultural thinking styles on the online decision-making processes for Hong Kong Chinese and European Canadians, with and without time constraints. We investigated the online decision-making processes in terms of (1) information search speed, (2) quantity of information used, and (3) type of information used. Results show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 43 publications
3
9
0
Order By: Relevance
“…However, our finding disagrees with the findings of Arshad and Ibrahim (2019) who reported that Pakistani investors gather and analyze more information as a strategy to reduce risk. Li, Masuda, and Russel (2014) also echoed similar findings with Arshad and Ibrahim in their study of online financial decisionmaking process of East Asian and North American countries that Hong Kong Chinese, compared to European Canadians, spend time to parse through information before making financial decisions. Hypothesis four sought to determine whether cultural factors affect investment decisions.…”
Section: Discussionsupporting
confidence: 80%
“…However, our finding disagrees with the findings of Arshad and Ibrahim (2019) who reported that Pakistani investors gather and analyze more information as a strategy to reduce risk. Li, Masuda, and Russel (2014) also echoed similar findings with Arshad and Ibrahim in their study of online financial decisionmaking process of East Asian and North American countries that Hong Kong Chinese, compared to European Canadians, spend time to parse through information before making financial decisions. Hypothesis four sought to determine whether cultural factors affect investment decisions.…”
Section: Discussionsupporting
confidence: 80%
“…Second, the current research suggests that alleviating the influence of dialectical beliefs may help to promote proenvironmental behaviors. Previous studies showed that the influence of dialectical beliefs diminished when people engaged in the decision that was important (vs. trivial; Li et al, 2014) or when they were reminded of time constraints (Li, Masuda, & Russell, 2015). Following these findings, future proenvironmental programs may develop some interventions that can foster the perceived importance of and time constraints associated with solving environmental issues, which may help alleviate the negative impact of dialectical beliefs on proenvironmental behaviors, which may eventually promote more proenvironmental behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…One key factor in differentiating holistic from analytic information processing is how much information is considered optimal (Choi, Dalal, Kim-Prieto, & Park, 2003;Li, Masuda, & Russell, 2015). For example, Choi et al (2003) found that when judging hypothetical murder cases, the more holistic Koreans took into consideration a greater amount of information than did European Americans or Asian Americans.…”
Section: Culture and Aestheticsmentioning
confidence: 99%